(untitled) (International Research in Economics and Finance, 2017)
Since the inception of prospects theory of Markowitz (1952) which leads to the development of CAPM has been studied and applied in many ways. Some researchers conclude that CAPM is valid and could be used for valuation of securities and cost of equity. However, critiques arise that CAPM is a single risk factor and remark that a single factor model cannot be generalized in the overall capital markets because the capital market absorbs many other risk factors. The CAPM has been applied to the Pakistan’s Stock Exchange to check the validity of CAPM for a sample of 306 individual firms and 18 industrial portfolios. Two pass regression has been applied to check the applicability of CAPM in Pakistan’s stock exchange. The results show that CAPM, single factor model is not valid for the technical analysis in Pakistan’s capital market. The investors need to use other type of factor models which include other economic and non economic kind of variables for valuation of securities.